THE IMPORTANCE OF GROWTH FACTORS IN THE DIAGNOSIS OF COLON CANCER - S. V. Volkov; S. V. Lobanov; P. P. Tereshkov (Сибирский онкологический журнал)
Objective: to determine the level of growth factors in the blood serum of patients with left-sided colon cancer and to assess the feasibility of using these findings in the tumor detection.Material and Methods. The study group included 63 patients aged 20 to 75 years who underwent surgery for left-sided colon adenocarcinoma (descending, sigmoid, rectosigmoid) with stage i (t1–2n0m0), ii (t3–4an0m0), and iii (t1–2n1m0). Only 5 patients developed metastases in one regional lymph node. The remaining patients had no regional metastases. In all patients, before hospitalization, the tumor was confirmed by colonoscopy followed by histological examination. The group of comparison consisted of 25 patients with chronic hemorrhoids without exacerbation, who underwent colonoscopy. In patients of the study group, blood tests were drawn on the day of surgery before its starting. In patients of the comparison group, blood was taken after excluding colon cancer (after colonoscopy). Blood tests were carried out using a test system (Biolegend): multiplex set for determining growth factors (angiopoietin-2, (ang-2), egf, epo, FGF-basic, G-csf, GM-csf, HGF, M-csf, pdgf-aa, pdgf-BB, scf, tgf-α, vegf).Results. In cancer patients, the levels of egf, HGF, M-csf, pdgf-aa, and pdgf-BB were several times higher than in the control group (p <0.05). The level of pdgf-aa was 10 times higher in cancer patients than in controls. In addition to quantitative changes, statistically significant differences were observed between the vegf level and sex of the patients; angio protein-2, G-csf, epo, M-csf, pdgf-aa, pdgf-BB, vegf levels and the age of the patients; tgf-α, HGF levels and the histological grade of the tumor.Conclusion. It was found that changes in the level of biologically active substances that occur in colon cancer can serve as additional diagnostic markers for cancer detection.